Progression-Free Survival and Patterns of Response in Patients With Relapsed High-Risk Neuroblastoma Treated With Irinotecan/Temozolomide/Dinutuximab/Granulocyte-Macrophage Colony-Stimulating Factor. Issue 3 (7th October 2022) - Lerman, Benjamin J.; Li, Yimei; Carlowicz, Cecilia; Granger, Meaghan; Cash, Thomas; Sadanand, Arhanti; Somers, Katherine; Ranavaya, Aeesha; Weiss, Brian D.; Choe, Michelle; Foster, Jennifer H.; Pinto, Navin; et al.
Abstract : PURPOSE: Although chemoimmunotherapy is widely used for treatment of children with relapsed high-risk neuroblastoma (HRNB), little is known about timing, duration, and evolution of response after irinotecan/temozolomide/dinutuximab/granulocyte-macrophage colony-stimulating factor (I/T/DIN/GM-CSF) therapy. PATIENTS AND METHODS: Patients eligible for this retrospective study were age < 30 years at diagnosis of HRNB and received ≥ 1 cycle of I/T/DIN/GM-CSF for relapsed or progressive disease. Patients with primary refractory disease who progressed through induction were excluded. Responses were evaluated using the International Neuroblastoma Response Criteria. RESULTS: One hundred forty-six patients were included. Tumors were MYCN -amplified in 50 of 134 (37%). Seventy-one patients (49%) had an objective response to I/T/DIN/GM-CSF (objective response; 29% complete response, 14% partial response [PR], 5% minor response [MR], 21% stable disease [SD], and 30% progressive disease). Of patients with SD or better at first post-I/T/DIN/GM-CSF disease evaluation, 22% had an improved response per International Neuroblastoma Response Criteria on subsequent evaluation (13% of patients with initial SD, 33% with MR, and 41% with PR). Patients received a median of 4.5 (range, 1-31) cycles. The median progression-free survival (PFS) was 13.1 months, and the 1-year PFS and 2-year PFS were 50% and 28%, respectively. The median duration of response was 15.9 months; the median PFS off all anticancer therapy was 10.4 months after discontinuation of I/T/DIN/GM-CSF. CONCLUSION: Approximately half of patients receiving I/T/DIN/GM-CSF for relapsed HRNB had objective responses. Patients with initial SD were unlikely to have an objective response, but > 1 of 3 patients with MR/PR on first evaluation ultimately had complete response. I/T/DIN/GM-CSF was associated with extended PFS in responders both during and after discontinuation of treatment. This study establishes a new comparator for response and survival in patients with relapsed HRNB.